Work in Progress. Filmgenetische Analyse der Anfangssequenzen - Kanzog, Klaus; Volkmer, Klaus (Germany, 2007)
The disc also contains: Work on "Class Relations" by Danièle Huillet and Jean-Marie Straub (1983, Harun Farocki) 65 min | How Merrily, Shall Laugh. Danièle Huillet and Jean-Marie Straub and Their Film "Class Relations" (1984, Manfred Blank) 42 min.
Subtitles: English, French.
Keywords: Documentary films